2005
DOI: 10.1110/ps.051750905
|View full text |Cite
|
Sign up to set email alerts
|

High yield bacterial expression of active c‐Abl and c‐Src tyrosine kinases

Abstract: The Abl and Src tyrosine kinases are key signaling proteins that are of considerable interest as drug targets in cancer and many other diseases. The regulatory mechanisms that control the activity of these proteins are complex, and involve large-scale conformational changes in response to phosphorylation and other modulatory signals. The success of the Abl inhibitor imatinib in the treatment of chronic myelogenous leukemia has shown the potential of kinase inhibitors, but the rise of drug resistance in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
258
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 210 publications
(269 citation statements)
references
References 21 publications
(19 reference statements)
5
258
0
Order By: Relevance
“…S1). All of the recombinant c-Abl proteins used in this study were coexpressed with the YopH phosphatase to prevent autophosphorylation of the activation loop and other sites (4,5,14). MS analysis showed that all of the myristoylated proteins were devoid of phosphotyrosine, whereas Ϸ25% of the Abl(NonMyr) molecules were phosphorylated on Y412 (MS/MS data not shown; see also Fig.…”
Section: Resultsmentioning
confidence: 97%
“…S1). All of the recombinant c-Abl proteins used in this study were coexpressed with the YopH phosphatase to prevent autophosphorylation of the activation loop and other sites (4,5,14). MS analysis showed that all of the myristoylated proteins were devoid of phosphotyrosine, whereas Ϸ25% of the Abl(NonMyr) molecules were phosphorylated on Y412 (MS/MS data not shown; see also Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Wild-type human c-Abl kinase domain (residues 248 -532) and mutant proteins were generated and purified as described previously (51). The drug-binding kinetics is measured by monitoring the decrease of protein fluorescence at 350 nm upon excitation at 290 nm on a HORIBA Jobin Yvon FluoroMax-3 spectrofluorimeter for 10 -20 half-lives of the transient, recorded by 1,000 -2,000 data points.…”
Section: Methodsmentioning
confidence: 99%
“…Wild-type HCK3D or the HCK3D.YEEI mutant were coexpressed in bacteria with YopH phosphatase and purified as described by Seeliger et al (30). The SH2 binding peptide (referred to as p2; sequence EPQ[pY]EEIPIKQ, where pY is phosphotyrosine) and the SH3 binding peptide (referred to as p3; sequence VSLARRPLPPLP) were synthesized in house.…”
Section: Methodsmentioning
confidence: 99%